High population frequencies of MICA copy number variations originate from independent recombination events - Klußmeier, Anja; Putke, Kathrin; Klasberg, Steffen; Kohler, Maja; Sauter, Jürgen; Schefzyk, Daniel; Schöfl, Gerhard; Massalski, Carolin; Schäfer, Gesine; Schmidt, Alexander H.; Roers, Axel; Lange, Vinzenz (Frontiers in immunology, 2023)
MICA is a stress-induced ligand of the NKG2D receptor that stimulates NK and T cell responses and was identified as a key determinant of anti-tumor immunity. The MICA gene is located inside the MHC complex and is in strong linkage disequilibrium with HLA-B. While an HLA-B*48-linked MICA deletion-haplotype was previously described in Asian populations, little is known about other MICA copy number variations. Here, we report the genotyping of more than two million individuals revealing high frequencies of MICA duplications (1%) and MICA deletions (0.4%). Their prevalence differs between ethnic groups and can rise to 2.8% (Croatia) and 9.2% (Mexico), respectively. Targeted sequencing of more than 70 samples indicates that these copy number variations originate from independent nonallelic homologous recombination events between segmental duplications upstream of MICA and MICB. Overall, our data warrant further investigation of disease associations and consideration of MICA copy number data in oncological study protocols.